Impact of personality traits on information needs and seeking behavior of LIS students in Pakistan. Issue 3 (19th August 2019) - Ahmed, Shamshad; Rehman, Farhat; Sheikh, Arslan
Abstract : Purpose: This paper aims to identify the personality traits (agreeableness, openness to experience, extraversion, conscientiousness and neuroticism) of library and information science (LIS) students in Pakistan. The difference among the personality traits of LIS students toward their information needs and seeking behavior is also analyzed. Design/methodology/approach: Two instruments, namely, BFI scale and a self-structured instrument were used to collect the data. Kruskal–Wallis test was applied to find out differences among the personality traits of LIS students toward their information needs and seeking behavior. Findings: Findings of the study revealed that out of 320 respondents, 186 possessed openness to experience, while only 7 possessed extraversion personality trait. Moreover, the students having extraversion personality trait were, generally, more concerned toward information needs. On the other hand students having conscientious trait were increasingly more seekers of information. Overall, the conscientiousness was identified as the most suitable personality trait for LIS students. A significant difference was also observed among all the personality traits of LIS students. Practical implications: The findings of this study will help in the identification of LIS individual's personality. The library managers can use these personality traits for the selection of suitable library professionals for their libraries. Originality/value: This study can be valuable for the induction of new library professionals and also help managers in assigning the duties based on these personality traits.